2019
DOI: 10.21608/jaauth.2019.91944
|View full text |Cite
|
Sign up to set email alerts
|

Exchange Rate Volatility and Tourism Stock Prices: Evidence from Egypt

Abstract: Tourism is a key stimulator of economic growth and foreign currency in Egypt. As an export sector, it could affect and be affected by changes in exchange rate. This paper investigates the dynamic relationship between exchange rate and tourism stock prices and examines the effect of exchange rate volatility on tourism stock prices in the Egyptian Exchange (EGX). Exchange rate is proxied by the USD/EGP official values. Granger causality test and ARCH/GARCH models are employed. Results provide an evidence of a un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
(27 reference statements)
1
3
0
Order By: Relevance
“…Indeed, investors are confident about the opportunities in MENA equities. This is similar to that of Ahmed (2019) and Hung (2020).…”
Section: Dynamic Relationships Between Equity and Currency Marketssupporting
confidence: 85%
See 1 more Smart Citation
“…Indeed, investors are confident about the opportunities in MENA equities. This is similar to that of Ahmed (2019) and Hung (2020).…”
Section: Dynamic Relationships Between Equity and Currency Marketssupporting
confidence: 85%
“…Their results show that currency fluctuation greatly impacted equity market movements in Tunisia and Turkey. Ahmed (2019) analyzes the relationship between EGP/USD and the EGX100 index using a nonlinear distributed lag autoregressive model. He found that the currency exchange rate seems to impact equity returns in the short and long term.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Muharam and Tussyadiah (2023) stated that exchange rate volatility may decrease tourism inflows, as international tourists may find difficulty in estimating prices in the destinations. The exchange rate has significant impact on the tourism industry's performance, including foreign tourist arrivals, travel costs, competitiveness, and corporate profits (Harb, 2019). Moreover, Soliman and Shedeed (2018) noted that when guests pay in dollars for hotel services, changes in the value of the dollar have a minor influence on purchasing power and hotel occupancy rate.…”
Section: The Impact Of Exchange Rate Change On the Hospitality Demandmentioning
confidence: 99%
“…The depreciation of the EGP against the other currencies presents a dual impact on the tourism industry. On one hand, the devaluation enhances the affordability of the Egyptian destination, potentially driving an increase in tourist demand (Abozied, 2021), and resulting in attract global tourism investments to Egypt (El Baradei, 2019;Harb, 2019). However, Muharam and Tussyadiah (2023) stated that exchange rate volatility may decrease tourism inflows, suggesting that tourists may face difficulties in estimating prices in volatile destinations.…”
Section: Introductionmentioning
confidence: 99%